Pengaruh Motivasi, Kompensasi, Gaya Kepemimpinan, Organization Citizenship Behavior (OCB), dan Disiplin Kerja terhadap Kinerja Karyawan Perhutani TPG 6 Petung Jember - Shevia Ichi Syahbana; Hayatul Maspufah; Mustofa Mustofa (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
The productivity of pine resin tappers is an important factor in supporting non-timber forest product management at Perum Perhutani. Human resource factors, including work motivation, compensation, democratic leadership style, Organizational Citizenship Behavior (OCB), and work discipline, are considered to influence employee performance. This study aims to analyze the effect of these variables on the performance of pine resin tappers at Perum Perhutani TPG 6 Petung, Jember. This research employed a quantitative approach using saturated sampling involving 95 active pine resin tappers. Data were analyzed using multiple linear regression supported by validity, reliability, classical assumption, t-test, and F-test analyses. The results show that work motivation, compensation, democratic leadership style, Organizational Citizenship Behavior (OCB), and work discipline have a positive and significant effect on employee performance, both partially and simultaneously. These findings indicate that improving human resource management is essential for enhancing the performance of pine resin tappers.